Leftover Opioid Analgesics and Disposal Following Ambulatory Pediatric Surgeries in the Context of a Restrictive Opioid-Prescribing Policy. (January 2022) - Stone, Amanda L.; Qu'd, Dima; Luckett, Twila; Nelson, Scott D.; Quinn, Erin E.; Potts, Amy L.; Patrick, Stephen W.; Bruehl, Stephen; Franklin, Andrew D.
Abstract : BACKGROUND: Opioid analgesics are commonly prescribed for postoperative analgesia following pediatric surgery and often result in leftover opioid analgesics in the home. To reduce the volume of leftover opioids and overall community opioid burden, the State of Tennessee enacted a policy to reduce initial opioid prescribing to a 3-day supply for most acute pain incidents. We aimed to evaluate the extent of leftover opioid analgesics following pediatric ambulatory surgeries in the context of a state-mandated restrictive opioid-prescribing policy. We also aimed to evaluate opioid disposal rates, methods of disposal, and reasons for nondisposal. METHODS: Study personnel contacted the parents of 300 pediatric patients discharged with an opioid prescription following pediatric ambulatory surgery. Parents completed a retrospective telephone survey regarding opioid use and disposal. Data from the survey were combined with data from the medical record to evaluate proportion of opioid doses prescribed that were left over. RESULTS: The final analyzable sample of 185 patients (62% response rate) were prescribed a median of 12 opioid doses (interquartile range [IQR], 12–18), consumed 2 opioid doses (IQR, 0–4), and had 10 opioid doses left over (IQR, 7–13). Over 90% (n = 170 of 185) of parents reported they had leftover opioid analgesics, with 83% of prescribed doses left over. A significant proportion (29%, n = 54 of 185) of parents administered no prescribed opioids after surgery. Less than half (42%, n = 71 of 170) of parents disposed of the leftover opioid medication, most commonly by flushing down the toilet, pouring down the sink, or throwing in the garbage. Parents retaining leftover opioids (53%, n = 90 of 170) were most likely to keep them in an unlocked location (68%, n = 61 of 90). Parents described forgetfulness and worry that their child will experience pain in the future as primary reasons for not disposing of the leftover opioid medication. CONCLUSIONS: Despite Tennessee's policy aimed at reducing leftover opioids, a significant proportion of prescribed opioids were left over following pediatric ambulatory surgeries. A majority of parents did not engage in safe opioid disposal practices. Given the safety risks related to leftover opioids in the home, further interventions to improve disposal rates and tailor opioid prescribing are warranted after pediatric surgery.